Stata and Dropbox. (September 2014) - Hicks, Raymond
Dropbox makes scholarly collaboration much easier because it allows scholars to share files across different computers. However, because the Dropbox directories have different pathnames for different users, sharing do-files can be complicated. In this article, I offer some tips on how to navigate pathnames in do-files when using Dropbox, and I present a command that automatically finds and changes to a user's Dropbox directory.